Utilisation of used palm oil as an alternative fuel in Thailand - Permchart, W.; Tanatvanit, S. (My University, 2007)
This paper summarises the overview of the current situation of alternative energies in Thailand. The utilisation of bio-diesel as an alternative energy in two economic sectors (i.e. transport and industrial sectors), which have the largest energy consumption in the country, is mainly presented because it has seemed to be the most promising project among various energy conservation projects of the Thai government. Actually, there is another bio-fuel project, namely, the ethanol project for blending with gasoline to produce gasohol (E10) used in gasoline engines, which has been developed and already become to an important policy for energy conservation of the country. Due to much more large number of diesel has been utilised, the bio-diesel project has been the first priority one to solve the petroleum crisis problems. However, it is remarked that the utilisation of bio-diesel as an alternative fuel seems to be unsatisfactory because of various reasons. Some issues in terms of both government policies and technical problems have not been clearly addressed. Therefore, this paper not only presents the utilisation of bio-diesel in these two sectors but also discusses the production processes, characterisations and some experimental testing results of bio-diesel. © 2007 American Institute of Physics.
Keywords: Alternative energy; Bio-diesel; Energy conservation project